Emerging role of PLAG1 as a regulator of growth and reproduction. Issue 2 (17th November 2015) - Juma, Almas R; Damdimopoulou, Pauliina E; Grommen, Sylvia V H; Van de Ven, Wim J M; De Groef, Bert
Abstract : Pleomorphic adenoma gene 1 (PLAG1) belongs to the PLAG family of zinc finger transcription factors along with PLAG-like 1 and PLAG-like 2. The PLAG1 gene is best known as an oncogene associated with certain types of cancer, most notably pleomorphic adenomas of the salivary gland. While the mechanisms of PLAG1-induced tumorigenesis are reasonably well understood, the role of PLAG1 in normal physiology is less clear. It is known that PLAG1 is involved in cell proliferation by directly regulating a wide array of target genes, including a number of growth factors such as insulin-like growth factor 2. This is likely to be a central mode of action for PLAG1 both in embryonic development and in cancer. The phenotype of Plag1 knockout mice suggests an important role for PLAG1 also in postnatal growth and reproduction, as PLAG1 deficiency causes growth retardation and reduced fertility. A role for PLAG1 in growth and reproduction is further corroborated by genome-wide association studies in humans and domestic animals in which polymorphisms in the PLAG1 genomic region are associated with body growth and reproductive traits. Here we review the current evidence for PLAG1 as a regulator of growth and fertility and discuss possible endocrine mechanisms involved.